IRS-Aided Radar: Enhanced Target Parameter Estimation via Intelligent Reflecting Surfaces - Esmaeilbeig, Zahra; Mishra, Kumar Vijay; Soltanalian, Mojtaba (Proceedings of the IEEE Sensor Array and Multichannel Signal Processing Workshop, 2022)
The intelligent reflecting surface (IRS) technology has recently attracted a lot of interest in wireless communications research. An IRS consists of passive reflective elements capable of tuning the phase, amplitude, frequency, and polarization of impinging waveforms. We investigate the deployment of IRS to aid radar systems when the line-of-sight (LoS) link to the targets is weak or blocked. We demonstrate that deployment of multiple IRS platforms provides a virtual or non-line-of-sight (NLoS) link between the radar and target leading to an enhanced radar performance. Numerical experiments indicate that the IRS enhances the target parameter estimation when the LoS link is weaker by \sim 10^{-1} in comparison to the NLoS link.